2018
DOI: 10.5194/acp-18-6293-2018
|View full text |Cite
|
Sign up to set email alerts
|

Low levels of nitryl chloride at ground level: nocturnal nitrogen oxides in the Lower Fraser Valley of British Columbia

Abstract: Abstract. The nocturnal nitrogen oxides, which include the nitrate radical (NO3), dinitrogen pentoxide (N2O5), and its uptake product on chloride containing aerosol, nitryl chloride (ClNO2), can have profound impacts on the lifetime of NOx (= NO + NO2), radical budgets, and next-day photochemical ozone (O3) production, yet their abundances and chemistry are only sparsely constrained by ambient air measurements. Here, we present a measurement data set collected at a routine monitoring site near the Abbotsford I… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 118 publications
(147 reference statements)
5
27
0
Order By: Relevance
“…industrial combustion, cooling towers, natural gas extraction, and suspension of road salt) and sea salt chloride transported inland. Further studies reported significant mixing ratios of ClNO 2 at a semi-rural site in continental Germany (Phillips et al, 2012(Phillips et al, , 2016 and at a mid-continental urban site in Canada (Mielke et al, 2011(Mielke et al, , 2016. Observations at continental sites could be reproduced by a global model (Wang et al, 2019) when considering the transport of HCl (aq), which had been initially formed in the gas phase through acid displacement in coastal regions.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…industrial combustion, cooling towers, natural gas extraction, and suspension of road salt) and sea salt chloride transported inland. Further studies reported significant mixing ratios of ClNO 2 at a semi-rural site in continental Germany (Phillips et al, 2012(Phillips et al, , 2016 and at a mid-continental urban site in Canada (Mielke et al, 2011(Mielke et al, , 2016. Observations at continental sites could be reproduced by a global model (Wang et al, 2019) when considering the transport of HCl (aq), which had been initially formed in the gas phase through acid displacement in coastal regions.…”
Section: Introductionmentioning
confidence: 92%
“…The formation of ClNO 2 can have a significant impact on regional NO x cycling and radical chemistry, especially in the polluted coastal and marine boundary layer (Simon et al, 2009;Riedel et al, 2014;Sarwar et al, 2014). The Cl atoms formed in Reaction (R2) can enhance oxidation rates of several volatile organic compounds (VOCs), especially during early morning hours (Phillips et al, 2012;Riedel et al, 2012a;Young et al, 2012) thus contributing to photochemical ozone production (Simon et al, 2009;Riedel et al, 2014;Sarwar et al, 2014;Faxon et al, 2015;Wang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…WBEA SO 2 data were used with a sampling interval of 5 min. Ozone and NO 2 mixing ratios were measured by UV absorption using a Thermo 49i O 3 monitor every 10 s and a blue diode laser cavity ring-down spectrometer every 1 s, respectively (data were averaged to 1 min; Odame-Ankrah, 2015; Paul and Osthoff, 2010). The slope uncertainties in these measurements were ±1 and ±10 %, respectively.…”
Section: Field Measurementsmentioning
confidence: 99%
“…The slope uncertainties in these measurements were ±1 and ±10 %, respectively. Radiometer measurements using a pair of spectral radiometers (one facing the zenith, the other the nadir direction) were used to determine actinic flux and to calculate photolysis frequencies (j values; Osthoff et al, 2018). Iron (Fe) and Manganese (Mn) were measured by semi-continuous X-ray fluorescence measurements of metals taken every hour on a filter tape with a measurement uncertainty of ±10 % (Phillips-Smith et al, 2017).…”
Section: Field Measurementsmentioning
confidence: 99%